Hand-washing promotion during Covid-19 outbreak in Riverbank of Kahayan River, Central Kalimantan, Indonesia - Missesa, Missesa; Viranti, Trissa; Kaswana, Shasa Dini Martha Ewa; Athena, Carolin Firsta; Nibel, Hendrowanto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
In mid-2020, COVID-19 cases in Central Kalimantan showed relatively high, approximately 10.5% of children suffered from COVID -19. Many institutions have been implementing health education on the positive healthy behaviour standard for COVID-19 prevention, including regular hand washing, mask-wearing, and social distancing. The purpose of this article is to give clear and actionable guidance for children living in river-basin residences. Central Kalimantan geographically has a number of rivers known as a watershed area (DAS). This photo essay records health promotion given during Covid-19 outbreak in Riverbank of Kahayan River, Central Kalimantan, Indonesia. In this study area, children use small boat made by wood to mobile or visit their friends to play. Before the Covid-19 Outbreak, using face mask in not compulsory and parents will just freely give permission to their children to play outside. It is shown that it is challenging to encourage children to protect themselves from the COVID-19 infection in the area of DAS. Moreover, the existence of this abundant water source is a potential natural asset for positive hygiene behaviour. Thus, it is worth noting that hand washing with soap and water is recommended. A cultural approach can also be an alternative for health campaigns. This paper shows how we use one of traditional musical instruments of Central Kalimantan, called Japen, and the lute is used as an instrument for making audio-visuals. This instrument is made from a sack. It includes education and has a key message of moral wisdom with the social value of the Dayak people in Borneo. Maintaining children's health during the Covid 19 pandemic with creative educational campaigns, using various modes such as posters, multimedia, and storytelling is beneficial for positive health behaviours.